MicroRNA expression profiles in human CD3+ T cells following stimulation with anti‑human CD3 antibodies - Sousa, Isabel Garcia (2017)
Background: Anti-CD3 therapy can induce immunosuppression by several non mutually exclusive mechanisms that have been proposed to explain the therapeutic effect the administration anti-CD3 mAb, but its immunoregulatory mechanism is still not completely clear. In T cells, microRNAs (miRNAs) regulate several pathways, including those associated with immune tolerance. Here, we report changes in miRNA expression in T cells following treatment with anti-human CD3 antibodies. Peripheral blood mononuclear cells were cultured in the presence of the monoclonal antibody OKT3 or a recombinant fragment of humanized anti-CD3. Following these treatments, the expression profiles of 31 miRNA species were assessed in T cells using TaqMan arrays. Results: Eight of the tested miRNAs (miR-155, miR-21, miR-146a, miR-210, miR-17, miR-590-5p, miR-106b and miR- 301a) were statistically significantly up- or down-regulated relative to untreated cells. Conclusions: Stimulation of T cells with anti-human CD3 antibodies alters miRNA expression patterns, including of miRNA species associated with immune regulatory pathways.